VD_FINDINFO HC / 2012 / 259 vom 8. März 2012 - VD Tribunal cantonal (2012)
PROTECTION DE L'UNION CONJUGALE, DROIT DE GARDE, ENFANT, OBLIGATION D'ENTRETIEN | 176 al. 1 ch. 1 CC, 176 al. 1 ch. 2 CC, 176 al. 3 CC